(The Study on Citrus Fruit Concentrate Processing) - Timur Antara, Ngakan; Suprianta, Dadang; Marliana, Nina (Warta Industri Hasil Pertanian, 1998)
The study on citrus concentrate processing has been carried out. Stages of treatment include washing of citrus fruit, peeling, extraction, filtration, concentration, formulation, bottling, pasteurization and storage. The treatment of the formulation were addition of resin, and addition of HFS and sugar. Observation were done on pH, total acid, the content of sugar, TSS, vitamin C, microbiology and organoleptic test. The results showed that the product formulated by adding of resin and sugars up to 40% met the Indonesian National Standard (SNI) of squash.